Insulin Resistance Unraveled: Hormonal Correlations in Gestational Diabetes: Hormones, Insulin Resistance, and Lipids in Gestational Diabetes - Chen, Siyu; Bai, Xuru; Yin, Xuerui; Bai, Lan (Journal of Medical Biochemistry, 2024)
Background: To investigate the correlation between the variations of cortisol and insulin-like growth factor 1 (IGF-1) and sex hormone binding globulin (SHBG) levels with insulin resistance and glucolipid metabolism in gestational glucose diabetics. Methods: The study included 110 pregnant women diagnosed with gestational diabetes mellitus in the GDM group,and 130 healthy pregnant women in the control group. Data collection,examination of relevant indexes,and comparison of differences in indexes between groups were conducted. Pearson correlation analysis was utilized to identify risk variables associated with GDM development,while binary logistic regression was employed to determine risk factors for GDM development. Results: The GDM group showed significantly greater levels of FPG,HbA1c,FINS,TG,FFA,Lp-PLA2,HOMA-IR,Cortisol,and IGF-1 compared to the control group (P<0.05),but considerably lower levels of SHBG,and HOMA-β. HOMA-IR was found to be positively correlated with FPG,HbA1c,FINS,TG,FFA,Lp-PLA2,Cortisol and IGF-1,whereas,negatively correlated with SHBG. FINS and SHBG were found to be independent protective factors for GDM (OR=0.463,0.801,P<0.05),whereas,HbA1c,TG,FFA,and gestational BMI were found to be independent risk factors for GDM (OR=1.992,4.234,1.990,1.629,P<0.05). Conclusion: SHBG,IGF-1,and Cortisol are all linked to glucose-lipid metabolism indices,and aberrant serum hormone expression is a major contributor to insulin resistance.